2017
DOI: 10.1155/2017/9502718
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing the Effectiveness of Electroacupuncture versus Medium‐Frequency Electrotherapy for Discogenic Sciatica

Abstract: Objective. To investigate the short- and long-term effects of electroacupuncture (EA) compared with medium-frequency electrotherapy (MFE) on chronic discogenic sciatica. Methods. One hundred participants were randomized into two groups to receive EA (n = 50) or MFE (n = 50) for 4 weeks. A 28-week follow-up of the two groups was performed. The primary outcome measure was the average leg pain intensity. The secondary outcome measures were the low back pain intensity, Oswestry Disability Index (ODI), patient glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…The results of this preliminary clinical study suggest that the analgesic action of acupuncture could be effective for postpartum sciatica, as manifested by the lower RDQ and VAS scores, and the higher patient‐reported prevalence of perceived recovery in the acupuncture group. While existing research has demonstrated that acupuncture is effective for sciatica in general, to our knowledge, this is the first report on acupuncture treatment for postpartum sciatica.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The results of this preliminary clinical study suggest that the analgesic action of acupuncture could be effective for postpartum sciatica, as manifested by the lower RDQ and VAS scores, and the higher patient‐reported prevalence of perceived recovery in the acupuncture group. While existing research has demonstrated that acupuncture is effective for sciatica in general, to our knowledge, this is the first report on acupuncture treatment for postpartum sciatica.…”
Section: Discussionmentioning
confidence: 80%
“…Particularly for sciatica, many studies have reported that acupuncture may be more effective than drugs in relieving leg pain and lumbago and improving global assessment
of sciatica and showed short‐term and long‐term benefits for this common disorder. Importantly, acupuncture has been demonstrated to be relatively safe and rarely associated with serious adverse effects in patients with sciatica .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,12 Some clinical trials and meta-analyses have recently contributed more evidence regarding acupuncture treatment for sciatica. [16][17][18] He et al, in their study of post-partum sciatica, revealed that up to 98% of patients in the treatment group recovered, compared with 24% in the non-acupuncture control group. 16 Zhang et al showed electroacupuncture had greater short-and long-term benefits for chronic discogenic sciatica than medium-frequency electrotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…16 Zhang et al showed electroacupuncture had greater short-and long-term benefits for chronic discogenic sciatica than medium-frequency electrotherapy. 17 Qiu et al also demonstrated that acupuncture may stimulate the sciatic nerve trunk and effectively relieve pain in patients with discogenic sciatica. 18 Moreover, acupuncture may reduce sciatica pain intensity, increase the pain threshold, 19 enhance the effects of drug, and improve outcomes.…”
Section: Introductionmentioning
confidence: 99%